Economic Restructuring at the District Level towards Sustainable Development - Thieu, Nguyen Manh; Loan, Phung Thanh (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Economic restructuring at the district level towards sustainable development is one of the important goals of the Party and the State. Looking back at the development process in recent years, it cannot be denied that Vietnam's economy has made significant progress. Attached to that development is the process of sustainable restructuring at the district level. Through a case study in Hoai Duc district, the author proposes sustainable development solutions for all levels within the district.